"ADOBO DIPLOMACY": LANGKAH BARU GASTRODIPLOMASI FILIPINA - Salsabila, Shafa (Multikultura, 2026)
Gastrodiplomacy is a popular instrument in today's cultural diplomacy. This gastronomic diplomacy was first implemented by Thailand through the "Global Thai" program, which successfully introduced Thai cuisine and culture to the international community. Among ASEAN countries, the Philippines is one that currently engages in gastronomic diplomacy, led by adobo as a staple dish. This study examines the Philippines' efforts to conduct gastronomic diplomacy through the lens of gastrodiplomacy theory. This study uses a qualitative method and draws on a literature review of journal articles, books, news, and social media. In 2025, the Philippines will intensify its efforts in conducting gastronomic diplomacy, especially with countries with which it has established close relations, such as South Korea, Vietnam, Bangladesh, and Australia. This gastronomic diplomacy is referred to as "Adobo Diplomacy" because adobo is the primary food promoted by the Philippine government in diplomatic contexts. The results of this study indicate that the Philippines' gastronomic diplomacy efforts align with the practical methods identified by Rockower (2020) following a literature review of previous studies.